Crime and Deterrence: Correlation Analysis - Bailey, William C. (1974)
A correlation analysis of the severity and certainty of punish ment and offense rates for the major index crimes produces results consistent with the predictions of deterrence theory. Certainty of punishment proves to be the chief deterrent for most crimes. Homicide, however, is influenced by severity, pos sibly reflecting the differences between homicide and other of fenses. Little evidence of interaction is found between certainty and severity in effects on crime rate. A powerfunction proves to better describe the relationship between the punishment varia bles and crime rates than a rectilinear equation-a conclusion which, even apart from the date, appears more reasonable than the reverse